Traid-bit embedding process on Arabic text steganography method - Roshidi Din; Reema Ahmed Thabit; Nur Izura Udzir; Sunariya Utama (Institute of Advanced Engineering and Science, 2021)
The enormous development in the utilization of the Internet has driven by a continuous improvement in the region of security. The enhancement of the security embedded techniques is applied to save the intellectual property. There are numerous types of security mechanisms. Steganography is the art and science of concealing secret information inside a cover media such as image, audio, video and text, without drawing any suspicion to the eavesdropper. The text is ideal for steganography due to its ubiquity. There are many steganography embedded techniques used Arabic language to embed the hidden message in the cover text. Kashida, Shifting Point and Sharp-edges are the three Arabic steganography embedded techniques with high capacity. However, these three techniques have lack of performance to embed the hidden message into the cover text. This paper present about traid-bit method by integrating these three Arabic text steganography embedded techniques. It is an effective way to evaluate many embedded techniques at the same time, and introduced one solution for various cases.